2016
DOI: 10.1177/0309364614556838
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory phenomenological study exploring the experiences of people with systemic disease who have undergone lower limb amputation and its impact on their psychological well-being

Abstract: An understanding of how the experience of living with an amputation and a chronic condition may change over time will help clinicians to identify the ongoing need for counselling support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…Regardless of etiology, a leg amputation is usually followed by major physical and psychosocial challenges that severely influence the person concerned (Murray & Forshaw, 2013;Norlyk, Martinsen, & Kjaer-Petersen, 2013;Ostler, Ellis-Hill, & Donovan-Hall, 2014;Washington & Williams, 2016). Reduced quality of life (Davidson, Khor, & Jones, 2010;Remes et al, 2010), significantly higher levels of social isolation, depression, and post-traumatic disorder (Horgan & MacLachlan, 2004;Remes et al, 2010) are reported particularly in the first year after the amputation (Phelps, Williams, Raichle, Turner, & Ehde, 2008).…”
Section: Articlementioning
confidence: 99%
“…Regardless of etiology, a leg amputation is usually followed by major physical and psychosocial challenges that severely influence the person concerned (Murray & Forshaw, 2013;Norlyk, Martinsen, & Kjaer-Petersen, 2013;Ostler, Ellis-Hill, & Donovan-Hall, 2014;Washington & Williams, 2016). Reduced quality of life (Davidson, Khor, & Jones, 2010;Remes et al, 2010), significantly higher levels of social isolation, depression, and post-traumatic disorder (Horgan & MacLachlan, 2004;Remes et al, 2010) are reported particularly in the first year after the amputation (Phelps, Williams, Raichle, Turner, & Ehde, 2008).…”
Section: Articlementioning
confidence: 99%
“…It is also common that patients experience emotional distress and require emotional support alongside the medical management of their DLEA (Horgan and MacLachlan, 2004;Liu et al, 2010;Senra et al, 2012;Dunne et al, 2014;Grech and Debono, 2014;Delea et al, 2015). In particular, major amputation is reported to compromise patients' body image and their relationships with others (Coffey et al, 2009;Norlyk et al, 2013;Holzer et al, 2014;McDonald et al, 2014;Siersma et al, 2014), while patients with minor amputation often require re-amputation due to wound-related complications, such as wound dehiscence and prolonged healing times (Pollard et al, 2006;Dudkiewicz et al, 2009;Kono and Muder, 2012;Vogel et al, 2014;Chan et al, 2019), which also affect the process of rehabilitation (Price et al, 2015). Post-amputation wound healing is generally challenging in the first 12 months after amputation, as wound healing rate is only achieved in less than half of the whole amputee population (Chan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Efforts to implement routine screening for selected patients could decrease the rAAA mortality rate. Screening programs for AAA are used in several countries [2], selecting patients based on age, sex, or cardiovascular risk profile. However, screening is costly and typically requires separate hospital visits.…”
Section: Discussionmentioning
confidence: 99%